PLATFORMS, PROBLEMS AND SOLUTIONS OF ONLINE ENGLISH LANGUAGE TEACHING AT VOCATIONAL HIGH SCHOOL - Fajar Kristina; Syahrial Syahrial; Wisma Yunita (BASIS (Bahasa dan Sastra Inggris), 2021)
The study aimed to discover and to describe online learning platforms used, the problems faced and the solutions that offered by the English teacher in Vocational High School. The descriptive qualitative research was used as the research design in order to describe in detail the issues which had been discovered. The researcher selected 7 English teachers from each state vocational high school of Bengkulu city as the representative sample for this research. The instrument of this research was the interview guideline and data were collected by using the interview. After collecting the data, the researcher analyzed the data by using descriptive analysis. The result Google classroom and WhatsApp were effective platforms to have online English language teaching in the pandemic era, especially, for the students at the vocational high school. The problems of using the platforms were the internet connection, lack of students’ motivation, lack of students’ understanding, and inefficient teaching time. While the problems of teaching language skills through the use of platforms were miss understanding and lack motivation, in adequate time, lack of interaction, and overload the use of data plan. The solution that the teacher used for solving the use of platform were providing the extended time and offline module or having face to face class. However for solving the problems of teaching language skills, the teachers did Whatsapp discussion, peer feedback and having question and answer session in Whatsapp, decreasing listening activity and providing additional time for writing.